Design and comparative analysis of inexact speculative adder and multiplier - Hari Kishore, K; K. V.Prasad, B; Manoj Sai Teja, Y; Akhila, D; Nikhil Sai, K; Sravan Kumar, P (International Journal of Engineering and Technology, 2018)
A Carry look ahead adder is a sort of the summer used in the logic design of the digital systems. The CLA boost up the speed by decreasing the measure of duration needed to calculate the carry bits. The CLA based outline of the inexact speculative adder is pipelined architecture to incorporate couple of logic paths along its basic way and in this manner, improving the recurrence of operation. This paper presents the comparative analysis of the pipelined inexact speculative adder and the general carry look ahead adder and showed that the delay is reduced to 48.27% when compared to carry look ahead adder and also we have designed the pipelined multiplier using the Inexact speculative adders and observed that the delay Â is reduced to 48.32% when compared to the normal multiplier. This entail Xilinx ISE Design Suite 14.5 Tool.